Apolipoprotein-A-I for severe COVID-19-induced hyperinflammatory states: A prospective case study - Faguer, Stanislas; Del Bello, Arnaud; Danet, Chloé; Renaudineau, Yves; Izopet, Jacques; Kamar, Nassim (Frontiers in Pharmacology, 2022)
Viral infections can promote cytokine storm and multiorgan failure in individuals with underlying immunosuppression or specific genetic background. Hyperinflammatory states, including critical forms of COVID-19, are characterized by a remodeling of lipide profile including dramatic decrease of the serum levels of apolipoprotein-A-I (ApoA-I), a protein known for its capacity to reduce systemic and lung inflammation, modulate innate and adaptative immunity and prevent endothelial dysfunction and blood coagulation. In this study, four immunocompromised patients with severe COVID-19 cytokine storm that progressed despite standard-of-care therapy (omicron (n=3) and delta (n=1) variants) received 2 to 4 infusions (10 mg/kg) of CER-001 an ApoA-I-containing HDL mimetic. Injections were well tolerated with no serious adverse events. Three patients treated while not on mechanical ventilation had early clinical and biological improvement (oxygen withdrawal and correction of hematological and inflammatory parameters, including serum levels of interleukine-8) and were discharged from the hospital 3 to 4 days after CER-001 infusions. In the fourth patient who received CER-001 after orotracheal intubation for acute respiratory distress syndrome, infusions were followed by transient respiratory improvement before secondary worsening related to ventilation-associated pneumoniae. This pilot uncontrolled exploratory compassionate study provides initial safety and proof-of-concept data from patients with COVID-19 cytokine storm receiving ApoA-I. Further randomized controlled trial evaluation is now required to ascertain whether ApoA-I has any beneficial effects in patients with COVID19 cytokine storm.